2008
DOI: 10.1080/02688690802308687
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy as an adjuvant in the management of intracranial meningiomas: are we practising evidence-based medicine?

Abstract: Although increasingly used, the precise role of radiotherapy in the management of meningiomas is still disputed. The objective of this study, therefore, was to appraise the evidence for adjuvant radiotherapy in benign and atypical intracranial meningiomas, and to compare and contrast it with the current opinion and practice of neurosurgeons in the United Kingdom and the Republic of Ireland. The use of radiotherapy as a primary treatment strategy or its use in the treatment of recurrence was not considered. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…A particularly controversial management issue is the role of RT for WHO grade II meningioma treated with MGTR. The treatment approach has largely been extrapolated from data on other meningioma grades, leading to non-uniform practices across institutions, adjuvant RT being used in many centres after subtotal resection of grade I I meningioma [27,28]. According to Kaur et al, the median 5-year survival of patients with atypical meningioma treated by RT was 67.5 % and ranged from 51 to 100 % [28].…”
Section: Surgery and Tumour Locationmentioning
confidence: 99%
“…A particularly controversial management issue is the role of RT for WHO grade II meningioma treated with MGTR. The treatment approach has largely been extrapolated from data on other meningioma grades, leading to non-uniform practices across institutions, adjuvant RT being used in many centres after subtotal resection of grade I I meningioma [27,28]. According to Kaur et al, the median 5-year survival of patients with atypical meningioma treated by RT was 67.5 % and ranged from 51 to 100 % [28].…”
Section: Surgery and Tumour Locationmentioning
confidence: 99%
“…34,41,49 Three retrospective studies advocated the use of adjuvant EBRT after GTR of AM (Table 3). 2,3,45 These studies reported improved LC or a trend toward improved LC with adjuvant EBRT and GTR versus GTR alone (p = 0.04, p = 0.09, and p = 0.10; tine adjuvant EBRT after GTR (Table 3).…”
Section: Adjuvant Ebrt After Gtrmentioning
confidence: 99%
“…There are numerous series in literature, describing surgical approaches to skull base and posterior fossa, explaining challenging parts of those surgeries and neuro-functional results (2,5,14,16,22,(38)(39)(40)41,44,45). However, many of those series were published when the SRS was not so common (32). In our series, nearly 52.1% of all meningiomas were located in the skull base or posterior fossa.…”
Section: Group Comparisonsmentioning
confidence: 52%